DETERMINATION OF TRICHOPHYTOSIS OF CATTLE BY POLYMERASE CHAIN REACTION METHOD - Umitzhanov, M.; Abdiramanova, B. A.; Moldakhanov, Y. S.; Akimzhan, N. A. (Zkatu im. Zhangirhana, 2024)
In recent years, the increasing veterinary and biomedical importance of dermatomycosis infection, in particular fungi of the genus Trichophyton, has been noted everywhere. This is due to the increased incidence of diseases caused by them, as well as their atypical forms, which are difficult to differentiate with mycoses of other etiologies and diseases of non-fungal origin. At the same time, the importance of laboratory diagnostic methods increases significantly; however, in practice, their actual informativeness is relatively low due to the slow growth of dermatomycosis pathogens on nutrient media and the frequent formation of atypical forms of these fungi as a result of previous (usually local) antifungal therapy. In this regard, the need for new, more effective ways of detecting dermatomycetes in biological substrates and methods of their identification is of particular importance. In this context, molecular genetic diagnostic technologies based on polymerase chain reaction seem to be the most promising, as it has been shown that they combine both high specificity and high sensitivity and can be used for reliable species-specific detection of some dermatomycosis pathogens. The data obtained indicate a significantly higher diagnostic efficiency, sensitivity and specificity of the PCR method for detecting Tr. verrucosum in clinical material compared with microscopic and cultural methods. These substantiate the need for widespread introduction of molecular genetic studies into the laboratory diagnosis of mycoses, as well as the need to optimize the laboratory component of the diagnostic subsystem not only for epizootological (epidemiological), but also for veterinary supervision and control of trichophytia. This is due to the well-known fact that animals are the main sources of infection for humans. In this regard, the adequate implementation of both types of surveillance (epidemiological and veterinary) requires, in each specific case of trichophytia, PCR detection of the pathogen, for the objective identification of epizootological (epidemiological) links between sources of infection, factors and routes of infection, identification of contaminated objects. At the same time, time costs can be significantly reduced and it becomes possible to express detection of the pathogen in various clinical samples.
Umitzhanov, M. Determination of trichophytosis of cattle by polymerase chain reaction method / M. Umitzhanov, B. A. Abdiramanova, Y. S. Moldakhanov, N. A. Akimzhan [et al.]. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - № 4-1 (77). - Р. 275-289 (Uralsk).
Keywords: Trichophyton verrucosum; polymerase chain reaction; sensitivity; specificity; diagnostic efficiency